Customers satisfaction towards maintenance management in a government hospital building in Malaysia / Mirdeeliana Amir - Amir, Mirdeeliana (2012)
Hospital is a complex building that operates 24 hours a day and the most difficult largely public sector buildings to maintain. The effectiveness of government hospital is affected by several factors, including the hospital maintenance quality. This research is attempts to look into the customers' satisfactions towards the maintenance management performance for (3) three government hospital buildings that has been awarded to three (3) local service providers. Three (3) hospitals building that managed by three (3) different service providers, which is Faber Mediserve Sdn Bhd, Radicare (M) Sdn Bhd and Pantai Medivest Sdn Bhd involved in this study. Data were collected through questionnaire surveys due to the possible subjects move around the building during the course of their work. A total of 100 respondents from each hospital were selected as the respondents to fill up the End User's Satisfaction Questionnaire. The data collected are analyzed by mean index. The findings signify that the customers are almost satisfied with the maintenance of the government hospital buildings. In contrast, low satisfaction could be found from the items related to the quality of time i.e. 'whether requested work is completed by the time it is needed'. In general, the satisfaction level among the respondents from three (3) hospitals is 'average satisfied'.